(untitled) (Ameghiniana, 2013)
Materials of a Hadrosaurian Dinosaur (Ornithischia; lguanodontoidea; Ornithopoda), of Danian (or perhaps. Upper-Maestrichtian) beds found in the Rio Negro Province (Patagonia) are presented. They are assigned, with some hesita’tion, to a representative of the flat-headed group of these curious animals known as "duck-billed" Dinosaurs. The author discusses its geological age, specially witli relation to the problem of the marine ingressions known as "Rocanense" I and II (and other names accepting a Danian age (Lower-Paleocene) of the Rocanense in its type locality near the Boca town. From a zoogeographic and phylogenetic view, the· author remarks that ’this· is· the first discovery of a Dinosaur of the family (and superfamily) made in the Southem Hemisfere. He discusses its origin and dispersal, in connection with ilie now available data on palaeotemperatures based on the study of pelagic foraminifera. Finally tl1e ·interest of the probable presence of a Tertiary Dinosaurian is remarked, emphasizing the lack of value of negative registers.